Citizenship Law in Africa A Comparative Study (3rd edition) - Manby, Bronwyn (African Minds, 2016)
Few African countries provide for an explicit right to a nationality. Laws and practices governing citizenship effectively leave hundreds of thousands of people in Africa without a country. These stateless Africans can neither vote nor stand for office; they cannot enrol their children in school, travel freely, or own property; they cannot work for the government; they are exposed to human rights abuses. Statelessness exacerbates and underlies tensions in many regions of the continent. Citizenship Law in Africa, a comparative study by two programs of the Open Society Foundations, describes the often arbitrary, discriminatory, and contradictory citizenship laws that exist from state to state and recommends ways that African countries can bring their citizenship laws in line with international rights norms. The report covers topics such as citizenship by descent, citizenship by naturalisation, gender discrimination in citizenship law, dual citizenship, and the right to identity documents and passports. It is essential reading for policymakers, attorneys, and activists. This second edition includes updates on developments in Kenya, Libya, Namibia, South Africa, Sudan and Zimbabwe, as well as minor corrections to the tables and other additions throughout.